Nlrp3: an immune sensor of cellular stress and infection - Lamkanfi, Mohamed (2010)
Innate immune cells rely on pathogen recognition receptors such as the nucleotide-binding and oligomerization domain (NOD)-like receptor (NLR) family to mount an appropriate immune response against microbial threats. The NLR protein Nlrp3 senses microbial ligands, endogenous danger signals and crystalline substances in the cytosol to trigger the assembly of a large caspase-1-activating protein complex termed the Nlrp3 inflammasome. Autoproteolytic maturation of caspase-1 zymogens in the Nlrp3 inflammasome leads to maturation and extracellular release of the pro-inflammatory cytokines interleukin (IL)-1β and IL-18. Gain-of-function mutations in the NOD domain of Nlrp3 are associated with auto-inflammatory disorders characterized by skin rashes and prolonged episodes of fever. In addition, decreased Nlrp3 expression was recently linked with susceptibility to Crohn’s disease in humans. In this review, we discuss recent developments on the role of the Nlrp3 inflammasome in innate immunity, its activation mechanisms and the auto-inflammatory disorders associated with deregulation of Nlrp3 inflammasome activity.